Žitomislić Monastery in the 19th Century - Milošević, Borivoje M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The Žitomislić Monastery, located not far from Mostar, has been considered one of the most important centres of Serbian spirituality and culture in Herzegovina since its founding. For this reason, it was the subject of extensive scientific research, while the nineteenth century was overlooked due to the lack of primary historical sources. Valuable descriptions of the monastery, providing details about its status and brotherhood, were left by Serafim Šolaja, Nićifor Dučić, and the Russian consul, Aleksandar Giljferding. The beauty of the monastery and its location along the Neretva River, on the way from Mostar to the coast, piqued the interest of many travellers, who left several records about it. A special place in the history of Žitomislić, and Serbian education in general, is held by the Spiritual School, the first of its kind in Bosnian Pashaluk, founded in 1858 by Nićifor Dučić and Serafim Perović. Like other Serbian monasteries and churches in Herzegovina, the Žitomislić Monastery survived the second half of the 19th century with occasional help from Serbia and Russia. Of special historical importance were the connections of Žitomislić with the Russian consuls in Bosnian Pashaluk.